2023
DOI: 10.1186/s12903-023-03537-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lip position on esthetics perception with respect to profile divergence using silhouette images

Abdulrahman K. Alshammari,
Muteb A. Algharbi,
Sulaiman K. Alshammari
et al.

Abstract: Background The aim of the study was to determine the facial divergence and lip position combinations that are most and least preferred, and to investigate whether age or gender has an impact on these preferences. Methods The current investigation was carried out on a sample of 1077 individuals who were not experts in the field (253 men and 824 females). The research employed black silhouette photographs of profiles featuring different lip locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The results indicate that protrusive lower lips are seen more in males and retrusive lips are seen more in females in preschool and school-going age. The sexual dimorphism regarding lip length, volume, and structure has been mentioned in a plethora of previously documented literature [ 5 , 8 , 16 - 20 ]. Mamandras et al found significant sexual dimorphism and inferred that male lips are larger than female in all measurements [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that protrusive lower lips are seen more in males and retrusive lips are seen more in females in preschool and school-going age. The sexual dimorphism regarding lip length, volume, and structure has been mentioned in a plethora of previously documented literature [ 5 , 8 , 16 - 20 ]. Mamandras et al found significant sexual dimorphism and inferred that male lips are larger than female in all measurements [ 21 ].…”
Section: Discussionmentioning
confidence: 99%